Ação coletiva e movimento GLBT em Goiânia - URANY, Alírio Melo (2008)
This paper conducts an investigation of the collective action organized by the LGBT movement in Goiania, seeking to demystify the character of uniqueness attributed to it, giving rise to the development of an interpretive framework capable of perceiving the plurality of actors and logics of action. I use Bourdieu's concept of habitus to view the process of aggregation of individuals, as well as the formation of homosexual identities positioned in a relationship of rulers and ruled in a heteronormative hegemonic social order. But how to systematize the LGBT movement in Goiania seeks to promote the struggle for positive recognition, is to present a breakdown of its social power into internal, semi-external and external. This allows you to view a schematic circuit energies of formation of networks of solidarity, used to maintain the cohesion of the social force within the field of LGBT activism. It is also evident that the agents are not in harmony, since that produce new hierarchies within the field of activism LGBT, but also tend to control the voltages to allow the maintenance and expansion of the field.